A new index for the strength analysis and prediction of cement-mixed soils. Issue 4 (12th March 2023) - Pham, Tuan A.; Kyokawa, Hiroyuki; Koseki, Junichi; Dias, Daniel
Abstract: In geotechnical projects involving soft soils, cement-mixed soils are an excellent way to improve the mechanical behaviour and engineering performance of soils. The water-to-cement ratio, cement content, and porosity are the most critical parameters impacting the strength of cement-mixed soils, but their effects are less well understood. The proportional influence of cement amount, porosity, and moisture content on cement-mixed soil strength is investigated in this research. The results showed that as the water-to-cement ratio increases, the influence of cementation and porosity on unconfined compressive strength decreases. The blended volume ratio is proposed as a new and adequate index for evaluating cement-mixed soil strength based on the experimental results. The blended volume ratio is the product of the void/cement volume ratio and the water/cement volume ratio. While the current index has not fully addressed the important effects of the water-to-cement ratio and porosity, the blended volume ratio allows describing the concurrent influences of porosity, cement amount, and water amount on the strength development. The experimental results showed that the cement-mixed soil strength is a function of the blended volume ratio. An empirical equation based on the blended volume ratio was then proposed for predicting the strength of cement-mixed soils. The validation of the proposed equation is verified by strength analysis for several different test data sets. A good agreement between measured and predicted results indicated that the proposed model is applicable to predict well the strength of cement-mixed soils.